Metabolic engineering of hairy root cultures in Beta vulgaris for enhanced production of vanillin, 4-hydroxybenzoic acid, and vanillyl alcohol - Husain, Zakir; Warsi, Zafar Iqbal; Khan, Sana; Mahendran, Ganesan; Afroz, Shama; Chandran, Ashish; Kashyap, Praveen Kumar; Khatoon, Kahkashan; Parween, Gazala; Tandon, Sudeep; Rahman, Laiq Ur (Frontiers in Bioengineering and Biotechnology, 2024)
The flavor of vanilla is a complex blend of compounds, with vanillin as the most prominent, along with vanillyl alcohol and 4-hydroxybenzoic acid. Natural vanillin extracted from vanilla beans is expensive, so researchers use heterologous synthesis to produce nature-identical vanillin in plant hosts. Consequently, alternative traditional farming and gathering methods are required to bridge the significant disparity between supply and demand. The current research successfully developed a method to induce hairy root formation from leaves. It integrated the Vanillin synthase (VpVAN) gene into transgenic hairy root lines of Beta vulgaris, synthesizing vanillin-related compounds. The presence of the VpVAN gene in transgenic roots was confirmed using PCR analysis. Additionally, RT-qPCR analysis demonstrated the expression of the VpVAN gene in the transgenic root lines. The transgenic hairy root clones H1, H2, and H5 showed enhanced vanillin production, vanillyl alcohol, and 4-hydroxybenzoic acid. Elicitation with methyl jasmonate (MJ) and salicylic acid (SA) further improved the production of these compounds in B. vulgaris hairy roots. The maximum hairy root biomass was observed after 60 days, with the maximum synthesis of vanillin and 4-hydroxybenzoic acid obtained from hairy root clones H5 and HR2, respectively.Vanillyl alcohol HR2 was obtained on the 45th day of cultivation. Elicitation with woundassociated hormone methyl jasmonate and salicylic acid enhanced the yield of vanillin, vanillyl alcohol, and 4-hydroxybenzoic acid, with a 215-fold increase in vanillin, a 13-fold increase in vanillyl alcohol, and a 21 fold increase in 4-hydroxybenzoic acid. The study results indicate that establishing transgenic hairy root cultures with the VpVAN gene is a promising alternative method for enhancing the production of vanilla flavor compounds such as vanillin, vanillyl alcohol, and 4hydroxybenzoic acid. A cost-effective protocol has been developed to mass-produce phenolic compounds using a hairy root culture of B.vulgaris. This approach addresses the increasing demand for these substances while reducing the cost of natural vanillin production, making it suitable for industrial-scale applications.